Faculty of Pharmacy’s visit to BSC Elder Care to foster future collaborations / Nurul Alyaa Ibrahim - Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2024)
On 12th September 2024, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Bertam Campus had its first visit to the Bagan Specialist Center (BSC) Elder Care located at Butterworth, Penang. This meaningful visit aimed to foster collaboration and to plan for future corporate social responsibility (CSR) activities between the BSC Elder Care and the Faculty of Pharmacy. The delegation from UiTM was led by a senior lecturer, Dr. Wong Yuet Yen, who was welcomed by Dr. Cecilia Chan, a gerontologist and person in charge of BSC Elder Care. This visit was attended by 8 academic staffs and 3 clinical instructors. Dr. Cecilia welcomed the UiTM delegation by introducing the services and care provided at the elderly center, with a focus on the elderly with dementia. This visit offered valuable insights into the daily operations of the center and the challenges faced by organisations in managing the facility. This visit has opened new perspectives on understanding the needs of the elderly in nursing care homes and thus helps identify the expertise that the UiTM team can offer to this facility to ensure a meaningful contribution, particularly in the volunteering program.